Energy Sustainability, Energy Financing and Economic Growth in Nigeria - Onabote, Ademola; Jolaade, Ayobami; Osabohien, Romanus; Otobo, Oghenetega; Ede, Christian; Okafor, Victoria (International Journal of Energy Economics and Policy, 2020)
Increase in the global population growth has led to a simultaneous increased in demand for energy leading to increased fear of global warming. This situation has given the international community a cause for concern and as a result, countries are seeking alternative sources for cleaner and sustainable energy. The importance of utilising greener energy sources is evident in the United Nation's Sustainable Development Goals (SDGs), especially Goal 7, Target 2. This study examined the long-run relationship between economic growth, sustainable energy and the different financing options for sustainable energy in Nigeria. The Johansen Cointegration test was utilised in order to achieve this objective. The findings showed that different sources of sustainable energy and the different types of financing employed in Nigeria have different effects on the economic growth of Nigeria. A long-run relationship amongst all three variables was also established. These findings are an indication that with the right policies, SDG 7 could be achieved. Keywords: Sustainable Energy, Energy Financing, Economic Growth, SDGs, Nigeria. JEL Classifications: Q20, Q28, Q43 DOI: https://doi.org/10.32479/ijeep.9336